Simplifique expressao algébrica a seguir (x+y)² + (2x-y)²+(×+y).(×-y)
Soluções para a tarefa
Respondido por
1
Resposta:
= (6x^2 + y^2 - 2xy)
Explicação passo a passo:
(x+y)^2 + (2x-y)^2 + (x+y) . (x-y) =
(x^2 + 2xy + y^2) +
((2x)^2 - 4xy + y^2) +
(x^2 - xy + xy - y^2) =
x^2 + 2xy + y^2 + 4x^2 - 4xy + y^2 +x^2 - y^2 =
6x^2 + y^2 - 2xy
Perguntas interessantes
Inglês,
7 meses atrás
Administração,
7 meses atrás
Sociologia,
7 meses atrás
História,
8 meses atrás
Matemática,
8 meses atrás
Geografia,
1 ano atrás